Sumario - autor, Sin (FAISCA: Journal of High Abilities, 2006)
The purpose of this research is to construct a questionnaire with mathematical problems and validate it as a way to identify children with mathematical talent. The questionnaire is constituted by a set of problems of multiplicative structure and we have applied it in two groups of 30 children. The first group are gifted children because they score above the 70th percentile in the Raven Intelligence Test (RIT). The second group has obtained a score below the 75th percentile in the RIT. We compare the achievement of both groups in the questionnaire with their math scores and their achievement in the RIT. We conclude that the questionnaire of mathematical problems produces more differences between both groups than the results in the RIT and the qualifications in mathematics. Therefore it constitutes an instrument with greater capacity to discriminate children with mathematical talent.
Keywords: Mathematically gifted; problem solving; numerical thinking